Kaji banding pendapatan tunai dari dua cara penjualan ternak babi di Kecamatan Ende Kabupaten Ende - Servarius S. Naga; Matheos F. Lalus; Arnold Keban (Jurnal Peternakan Lahan Kering, 2019)
Ende subdistrict is one of the 21 subdistricts in Ende District. The pig selling in Ende District was conducted by two form those were live animal selling and meat selling. Selling price of the pig is determaind by live weight of the pig, consumen bought pig for raising, costume, party, and self consumphim. The pig wos slaughter not of Abetoran, meat selling is in the from of porsim. The ways of pig selling in fluence revenue and income. The objective of this research was to know the income of the two ways of selling. Method usedin in the research was survey method. The determaind of the sample village was conducted purposively by considering village applied the mont the two ways of pig selling. So that obtain three sample villages namely Nsetundora I, Ndetundora II, and Ndetundora III. The determation of sample farmer used simple random method. So that obtaimed 62 sample farmers (responden). Criteria was responden have raised pig over two years and have ever sold. The analyse used was income analysis and mean different test (t test). The result of the analysis indicated that mean income from animal live selling was Rp5.212.171/1AU, other wise mean income from meat selling was Rp.11.935.636/1AU. The result of t-test in dicated that there was very significant difference of mean income from two ways of pig selling. The condussion of this research was meat selling having higher mean income than animal live selling.